Monitoring the health of populations statistical principles and methods for public health surveillance - Brookmeyer, Ron.; Stroup, Donna F., 1951- (New York ; Oxford : Oxford University Press, 2004)
This text explores the critical issues in the statistical analysis and interpretation of public health surveillance data. It covers statistical methods for detecting disease outbreaks and clusters, the use of survey methods and interpreting time trends and geographic patterns, among other topics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health surveillance; Public health surveillance -- Statistical methods; Epidemiology